INFLUENCE OF PROMOTION OF POSITION AND DISCIPLINE ON PERFORMANCE IN EMPLOYEES AT PT CITRA KARYA JABAR TOL SUMEDANG REGENCY WEST JAVA - Dessy Sofyanty; Yudiyanto Joko Purnomo (Transpublika Publisher, 2022)
This study aims to identify and measure the performance of PT Citra Karya Jabar Tol in Sumedang Regency, West Java since the achievement of employee performance is an important thing that is implemented to produce maximum performance and can survive in the midst of global competition. This research was carried out at PT Citra Karya Jabar West Java Tol Road. This research uses descriptive research methods with a quantitative approach. The regression coefficient value for job promotion variable shows a positive value of 0.412 X1, it can be interpreted that if the promotion increases, the employee's performance will increase by 0.412 units. Furthermore, the discipline variable in the regression equation shows a positive value of 0.42 X2, it can be interpreted that if the discipline will increase by 0.412 units. In addition, the value of the determinant coefficient of R Square is 0.901 or 90.1%, meaning that the influence of the Position Promotion variable (X1) and the Discipline variable (X2) on Employee Performance at PT Citra Karya is 90'1%. Meanwhile, the remaining 9.9% is influenced by other factors beyond this study.